2020
DOI: 10.1055/s-0039-1690050
|View full text |Cite
|
Sign up to set email alerts
|

Oligoether-Substituted Derivatives of Carbon-Rich 1,4,7,10,13,16-Hexaethynyltribenzo[a,e,i]cyclododeca-5,11,17-triyne (C36H12) and 1,4,9,12-Tetrakis(ethynyl)dibenzo[a,g]cyclododeca-5,7,13,15-tetrayne (C28H8): Potential Precursors to the Circular [6]Phenylene (‘Antikekulene’) Frame

Abstract: The title compounds, in which the terminal alkyne functions are adorned with -CH2OCH2CH2OCH2CH2OCH2CH3 or -p-C6H4OCH2CH2 OCH2CH2OCH3 substituents, were synthesized. The strategies for their preparation relied on prior art and involved the use of Sonogashira alkynylations of appropriate haloarenes, Stephens–Castro cyclizations of 1,2,4-trialkynyl-3-iodobenzenes, and Hay oxidative couplings of 1,2,3,4-tetralkynylbenzenes. The targets form yellow materials, exhibiting yellow-green fluorescence, and they are very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…[1]­Acediynes can be synthesized via the Eglington coupling reaction of 1,2-diethynylbenzene (Scheme ). However, this reaction also produces several types of cyclic oligomers, such as tribenzodehydro[18]­annulene (trimer) and tetrabenzodehydro[24]­annulene (tetramer), as reported by Haley . We have previously reported the selective synthesis of tetrakis­(trimethylsilyl)[1]­acediyne via Eglington coupling of 1,4-bis­(trimethylsilyl)-2,3-diethynylbenzene (Scheme ), and only the desired silyl[1]­acediyne was produced without the formation of the cyclic oligomers .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…[1]­Acediynes can be synthesized via the Eglington coupling reaction of 1,2-diethynylbenzene (Scheme ). However, this reaction also produces several types of cyclic oligomers, such as tribenzodehydro[18]­annulene (trimer) and tetrabenzodehydro[24]­annulene (tetramer), as reported by Haley . We have previously reported the selective synthesis of tetrakis­(trimethylsilyl)[1]­acediyne via Eglington coupling of 1,4-bis­(trimethylsilyl)-2,3-diethynylbenzene (Scheme ), and only the desired silyl[1]­acediyne was produced without the formation of the cyclic oligomers .…”
Section: Introductionmentioning
confidence: 92%
“…In fact, significant molecular design efforts have been made to develop extended π–electron systems, such as annulenes, which have unique structures and properties . Among them, [ n ]­acediynes ( n = 1, 2, 3) (Figure ), linearly fused benzodehydro[12]­annulenes, have been investigated as a partial graphdiyne structure. Recently, studies regarding 2D and 3D molecular arrays of these annulenes have also been reported . On the other hand, only one report has been published thus far regarding the synthesis and absorption properties of high-order [ n ]­acediynes ( n = 2 and 3) .…”
Section: Introductionmentioning
confidence: 99%
“…Antikekulenes have posed considerable challenges and interest to synthetic chemists as all attempts to synthesize these antiaromatic compounds have failed up to now although their precursors have been successfully made in the lab [1][2][3][4]. Ever since the successful synthesis of kekulene, a molecule made by circumcision of coronene, several other holey analogs of kekulenes such as heptulenes, octulenes, and holey nanographenes in general, have been synthesized [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to carry out CpCo­(CO) 2 -mediated cyclotrimerization of an unstable oligoalkyne with the TBC’s framework (Vollhardt et al) and three-fold hydrosilylation of 1 with Karstedt’s catalyst (Mitzel et al) have been communicated. The lack of other reports on the use of 1 in other transition-metal-catalyzed reactions is not surprising because such reactions result in products with increased ring strain due to disruption of ideal bond angles and conjugation of the basic framework.…”
mentioning
confidence: 99%